Pengaruh Metode Drill And Pratice Terhadap Teknik Dasar Passing Futsal Pada Atlet Pemula - Ilham Ismail, Taopik; Kurniawati, Ani; Arifin, z. (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2024)
This study aims to determine the effect of the drill and practice training method on basic passing skills in futsal. The problem addressed is the lack of mastery in basic passing techniques due to limited training variations, which affects passing accuracy. This research uses an experimental method with a pretest-posttest design on a single group, with 15 beginner athletes from Planet Futsal as the research subjects. The test used is a rebound board test with a validity of 0.79 and a reliability of 1.80. Data analysis was performed using a t-test with a significance level of 0.05%. The results show that before treatment, the t-value = 2.43 > t-table = 3.52, and after treatment, the t-value = -16.33 < t-table = 2.76, with a Gain score of 0.47. In conclusion, the drill and practice training method improved passing skills by 47% in beginner athletes at Planet Futsal.